EMPOWERING EDUCATORS: THE ROLE OF TEACHER LEADERSHIP AND LEARNING COMMUNITIES IN ENHANCING LEARNING AGILITY - Istuningtyas Pramesti; Yovitha Yuliejantiningsih; Supriyono Purwosaputro (RADJA PUBLIKA, 2025)
The advancement of the digital era demands that teachers possess a high level of adaptability. However, in rural areas such as Limbangan Subdistrict, Kendal Regency, limitations in infrastructure and access to technology pose significant challenges. This study aims to examine the influence of teacher leadership and participation in learning communities on the learning agility of elementary school teachers. A quantitative approach with explanatory research design was employed, involving 137 teachers selected through proportionate stratified random sampling. Data were collected via an online questionnaire and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that teacher leadership has a positive and significant effect on learning agility (p < 0.05), while participation in learning communities does not show a significant partial effect. However, jointly, both variables have a significant influence on learning agility, contributing 67% to the variance. These findings highlight that strengthening teacher leadership is a key factor in enhancing adaptive learning capacity amid limitations. Meanwhile, participation in learning communities needs to be more strategically directed to have a tangible impact on professional development. This research contributes to the literature on teacher capacity development in rural areas and offers policy directions to support digital-based educational transformation.